Gelidium amansii Attenuates Hypoxia/Reoxygenation-Induced Oxidative Injury in Primary Hippocampal Neurons through Suppressing GluN2B Expression - Md. Abdul Hannan; Md. Nazmul Haque; Md. Mohibbullah; Raju Dash; Yong-Ki Hong; Il Soo Moon (MDPI AG, 2020)
Oxidative stress is known to be critically implicated in the pathophysiology of several neurological disorders, including Alzheimer’s disease and ischemic stroke. The remarkable neurotrophic activity of Gelidium amansii, which has been reported consistently in a series of our previous studies, inspired us to investigate whether this popular agarophyte could protect against hypoxia/reoxygenation (H/R)-induced oxidative injury in hippocampal neurons. The primary culture of hippocampal neurons challenged with H/R suffered from a significant loss of cell survival, accompanied by apoptosis and necrosis, DNA damage, generation of reactive oxygen species (ROS), and dissipation of mitochondrial membrane potential (ΔΨm), which were successfully attenuated when the neuronal cultures were preconditioned with ethanolic extract of G. amansii (GAE). GAE also attenuated an H/R-mediated increase of BAX and caspase 3 expressions while promoting Bcl-2 expression. Moreover, the expression of N-methyl-d-acetate receptor subunit 2B (GluN2B), an extrasynaptic glutamate receptor, was significantly repressed, while synaptic GluN2A expression was preserved in GAE-treated neurons as compared to those without GAE intervention. Together, this study demonstrates that GAE attenuated H/R-induced oxidative injury in hippocampal neurons through, at least in part, a potential neuroprotective mechanism that involves inhibition of GluN2B-mediated excitotoxicity and suppression of ROS production, and suggests that this edible seaweed could be a potential source of bioactive metabolites with therapeutic significance against oxidative stress-related neurodegeneration, including ischemic stroke and neurodegenerative diseases.